(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the time spent using smartphones and the relationship with myopia in ethnic boarding high school students. Subjects and methods: Cross-sectional descriptive study on 1558 students at 2 ethnic boarding high schools in Vinh city, Nghe An province from September 2023 to the end of March 2024. Results: All students use smartphones more than 1 hour/day, of which 56.58% of students use smartphones more than 3 hours/day, the average usage time is 3.36 hours/day. Female students have an average usage time of 4.08 hours/day, 3.02 hours/day higher than male students (p<0.05). The overall rate of myopia is 29.01% among ethnic boarding high school students. The prevalence of myopia is 19.81% in students who use the phone less than 2 hours a day, increasing to 22.87% of myopia in the group that uses the phone 2-3 hours a day and uses the phone more than 3 hours per day, the prevalence of myopia is 35.10%. The difference in increased phone usage time and increased myopia is statistically significant with p < 0.01. Time spent using the phone over 3 hours per day increases the risk of myopia with OR: 2.1 (95%CI: 1.65- 2.90) compared to using the phone less than 2 hours per day.